SEBARAN POPULASI DAN KONDISI TEMPAT TUMBUH BUNGA BANGKAI (AMORPHOPHALLUS SP) DI KAWASAN HUTAN KOTA GUNUNG SARI KOTA SINGKAWANG - Saragih, Edi Semjaya; Astiani, Dwi; Sisillia, Lolyta (JURNAL HUTAN LESTARI, 2016)
Urban forest is one component of green open spaces in a city. The existence of anurban forest serves in a hydrological system, creating a micro-climate, maintaining the balance of oxygen (O2) and carbon dioxide (CO2), reducing pollutants, and noises. Diversity of flora in urbant forest of Gunung Sari is not yet known for their distribution and the number of species. One of the flora that have not yet registered in term of their distribution and diversity isCarrion flowerÂ  (Amorpophallus sp). The purpose of this study was to determine the distribution and site condition of Amorphophallus, which found in the urban forest of Gunung Sari. The research was done by applying survey methods using transects withdirection perpendicular to contour lines. Data assessment of Carrion flower was surveyed using a 20 x 20 mcontinuous plots(10 m left and right side of transects) and 8 transectschosen were assumed torepresentthe entire urban forest conditions. Each transect length was500- 700 m. Only one species of carrion flower found, Amorphophallus hewittii Aldrew. Morista index analysis show that the pattern of distribusion of A. hewittii were found in a group, with the the index of 1.60. The Carrion seedling density was greater than the rate of adult density.Regression analysis resulted a relationship between the density of A. hewittii andlight intensity where it grown. The higher the intensity of incoming light in the forest of floor, the population A. hewittii was reduced. Keywords : Urban forest of Gunung Sari, habit, Amorphophallus.